iPhone Games Projects - Cabrera, PJ; Bondo, Joachim; Greenstone, Brian; Lee, Mike; Gotch, Jamie; Kasprzak, Michael; Zito, Richard; Aitken, Matthew; Hennessy, Olivier; Lee, James (Apress : Imprint: Apress, 2009)
One look at the App Store will show you just how hot iPhone games have become. Games make up more than 25 percent of all apps, and more than 70 percent of the apps in the App Store's Most Popular category. Surprised? Of course not! We've all filled our iPhones with games, and many of us hope to develop the next bestseller. This book is a collection of must-know information from master independent iPhone game developers. In it, you'll discover how some of the most innovative and creative game developers have made it to the pinnacle of game design and profitability. This book is loaded with practical tips for efficient development, and for creating compelling, addictive gaming experiences. And it's not all talk! It's supported with code examples that you can download and use to realize your own great ideas. This book's authors are responsible for some of the all-time most popular and talked-about games: Brian Greenstone developed Enigmo and Cro-Mag Rally. Aaron Fothergill developed Flick Fishing. Mike Lee developed Tap Tap Revolution, the most downloaded game in App Store history. Mike Kasprzak's Smiles was a finalist in the IGF 2009 Best Mobile Game competition. PJ Cabrera, Richard Zito, and Matthew Aitken (Quick Draw, Pole2Pole); Joachim Bondo (Deep Green); and Olivier Hennessy and Clayton Kane (Apache Lander) have received glowing reviews and accolades for their games. Pair iPhone Games Projects with Apress's best-selling Beginning iPhone Development: Exploring the iPhone SDK, and you'll have everything you need to create the next game to top the sales charts.